Bilateral versus single internal thoracic artery for coronary artery bypass grafting with end‐stage renal disease: A systematic review and meta‐analysis. Issue 4 (9th March 2019) - Tam, Derrick Y.; Rahouma, Mohamed; An, Kevin R.﻿; Gaudino, Mario F.L.; Karkhanis, Reena; Fremes, Stephen E.
Abstract: Background: The incidence of severe coronary artery disease (CAD) in patients with end‐stage renal disease (ESRD) on dialysis is high. Coronary artery bypass grafting (CABG) is the preferred treatment in those with severe CAD. Bilateral internal thoracic artery (BITA) vs single internal thoracic artery (SITA) grafting has been shown to improve late survival in other high‐risk populations. In ESRD, comparative studies are limited by sample size to detect outcome differences. We sought to determine the late survival and early outcomes of BITA compared with SITA in patients with ESRD. Methods: MEDLINE and EMBASE were searched from inception to 2017 for studies directly comparing BITA to SITA in patients with ESRD undergoing CABG. The primary outcome was late survival; secondary outcomes were in‐hospital/30‐day mortality, stroke, and deep sternal wound infection (DSWI). Kaplan‐Meier curve reconstruction for late mortality was performed. Results: Five studies (three adjusted [n = 197] and two unadjusted observational studies [n = 231]) were included in the analysis. Reported ITA skeletonization ranged from 83% to 100% (median: 100%). There was no difference in in‐hospital mortality (risk risk [RR], 0.84; 95% confidence interval [95%CI], 0.36, 1.98; P  = 0.70), perioperative stroke (RR, 1.97; 95%CI, 0.58, 6.66; P  = 0.28), and DSWI (RR, 1.56; 95%CI, 0.60, 4.07; P  = 0.36) between BITA and SITA. All studies reported adjusted late mortality, which was similar between BITA and SITA (incident rate ratio, 0.81; 95%CI, 0.59, 1.11) at mean 3.7‐year follow‐up. Conclusions: BITA grafting is safe in patients with ESRD although there was no survival benefit at 3.7 years. Additional studies with longer follow‐up are required to determine the potential late benefits of BITA grafting in patients with ESRD.